(untitled) (Cardiovascular Journal, 2021)
Background: Among the various options of treatment of ischemic heart disease coronary artery bypass grafting (CABG) remains one of the standard modes of revascularization. Coronary artery bypass grafting can be done with or without using cardiopulmonary bypass (CPB). This study was to compare postoperative early (up to 1 month) outcome of intact versus open pleura after off pump coronary artery bypass grafting (OPCAB). Methods: In this study, sixty patients aged 18-70 years admitted in Department of Cardiac Surgery, NICVD who underwent OPCAB were selected for the study sample and divided into two groups. Groups I (n=30) consist of the patients who underwent OPCAB with pleurotomy and Group II (n=30) consists of patients who underwent OPCAB with intact pleura. Outcome of patients including Forced expiratory volume in first second (FEV1) & Forced vital capacity were evaluated. Results: Patients having OPCAB with intact pleura showed lower incidence of atelectasis and pleural Effusion in 2nd postoperative & 5th postoperative day (p<0.05). Lower amount of chest tube drainage and transfusion requirement were observed in group II patients than Group I (530.00 ± 28.97 vs. 485.96±38.62; p<0.05 and 611.23±99.22 vs. 577.93±135.38, p>0.05, respectively). Moreover, higher duration of ventilation were noted in group I (7.50 ± 2.22 vs. 6.30±2.32, p<0.05). Beside these, total duration of ICU stay & hospital stay were significantly higher in patients OPCAB with open pleura (p<0.05). Conclusion: Keeping the pleura intact during OPCAB is significantly associated with low rate of atelectasis and pleural effusion. Clinically, it decreases postoperative amount of blood loss and significantly lowers ICU stay, mechanical ventilation time and hospital stay. Therefore, it can be concluded that intact pleura during OPCAB improves postoperative pulmonary outcomes. Cardiovasc. j. 2021; 13(2): 112-119